Analysis of Financial Stability In Indonesia’s Banking Sector And Its Determinant Factors - Mochammad Yusuf; Andika (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
This study analyzes the financial stability of Indonesia’s banking sector and the macroprudential factors influencing it over the period 2014–2024. Monthly time-series data obtained from Bank Indonesia and the Financial Services Authority (OJK) were processed using the Engle–Granger Error Correction Model (ECM) to examine both short-run and long-run relationships between inflation, interest rates, exchange rates, and money supply in relation to financial stability, which is measured through the Bank Z-score. The empirical findings reveal that inflation exerts a significantly negative impact on financial stability, while the policy interest rate has a significantly positive long-term effect. The money supply demonstrates a positive influence in the long run but a negative one in the short run, whereas the exchange rate shows no statistically significant effect. These results highlight the importance of maintaining credible monetary policy and adaptive macroprudential coordination to safeguard the resilience of Indonesia’s banking sector amid persistent global economic uncertainties.